2006
DOI: 10.1002/jbm.a.30630
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinked poly(ϵ‐caprolactone/D,L‐lactide)/bioactive glass composite scaffolds for bone tissue engineering

Abstract: A series of elastic polymer and composite scaffolds for bone tissue engineering applications were designed. Two crosslinked copolymer matrices with 90/10 and 30/70 mol % of epsilon-caprolactone (CL) and D,L-lactide (DLLA) were prepared with porosities from 45 to 85 vol % and their mechanical and degradation properties were tested. Corresponding composite scaffolds with 20-50 wt % of particulate bioactive glass (BAG) were also characterized. Compressive modulus of polymer scaffolds ranged from 190+/-10 to 900+/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 48 publications
1
32
0
1
Order By: Relevance
“…In 2003, Boccaccini and Maquet [42] reported for the first time on the successful fabrication of porous foam-like bioactive glass containing poly(lactide-co-glycolide) (PLGA) composites, which exhibited well-defined, oriented and interconnected porosity. Since then, many studies have been carried out to optimize and investigate bone TE composite scaffolds concerning material combinations, bioactive properties, degradation characteristics [161,164,165,168], in vitro [47,[161][162][163]169] and in vivo behavior [47,164], as well as mechanical properties [50,81,160].…”
Section: Bioactive Glass Containing Composite Scaffoldsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2003, Boccaccini and Maquet [42] reported for the first time on the successful fabrication of porous foam-like bioactive glass containing poly(lactide-co-glycolide) (PLGA) composites, which exhibited well-defined, oriented and interconnected porosity. Since then, many studies have been carried out to optimize and investigate bone TE composite scaffolds concerning material combinations, bioactive properties, degradation characteristics [161,164,165,168], in vitro [47,[161][162][163]169] and in vivo behavior [47,164], as well as mechanical properties [50,81,160].…”
Section: Bioactive Glass Containing Composite Scaffoldsmentioning
confidence: 99%
“…Extensive work has been also carried out to investigate the cellular response to bioactive glass containing composites concerning composition, particle concentration and particle size effect in vitro and in vivo [46][47][48][161][162][163][164]166,[169][170][171]174]. For example, Lu et al [179] showed that for PLGA/bioactive glass films (0, 10, 25, 50 wt %), the growth, mineralization and differentiation of human osteoblast-like SaOS-2 cells (Figure 15), as well as the kinetics of Ca-P layer formation and the resulting Ca-P chemistry were dependent on BG content.…”
Section: Bioactive Glass Containing Composite Scaffoldsmentioning
confidence: 99%
“…To carry out biological testing, the cell culture and histological laboratory, standard stainings and molecular biology techniques should be available, as well as several light microscopes and a computer-based histomorphometric analysis system (e.g. Aho et al, 2004;Meretoja et al, 2006;Puska et al, 2003;Silva Nykänen et al, 2011).…”
Section: Methods To Study Materials For Bone Reconstructionmentioning
confidence: 99%
“…Since the mid-1990s, biodegradable polymer composites appear to have been studied for the applications of tissue engineering Meretoja et al, 2006;Middleton & Tipton, 2000;Törmälä, 1992;Wang, 2003). In these, the typical matrix polymers are polylactide (PLA), polycaprolactone (PCL), polypropylenefumarate (PPF) or any of their copolymers.…”
Section: Biodegradable Polymers As Matrix Polymersmentioning
confidence: 99%
See 1 more Smart Citation